Clinical characteristics, treatment outcomes and potential novel therapeutic options for patients with neuroendocrine carcinoma of the prostate - Apostolidis, Leonidas; Nientiedt, Cathleen; Winkler, Eva C.; Berger, Anne Katrin; Kratochwil, Clemens; Kaiser, Annette; Becker, Anne-Sophie; Jäger, Dirk; Hohenfellner, Markus; Hüttenbrink, Clemens; Pahernik, Sascha; Distler, Florian A.; et al. (OncoTarget, 2019)
https://doi.org/10.18632/oncotarget.26523 Leonidas Apostolidis, Cathleen Nientiedt, Eva Caroline Winkler, Anne Katrin Berger, Clemens Kratochwil, Annette Kaiser, Anne-Sophie Becker, Dirk Jäger,...
Gesehen am 02.04.2020